Woolly oak aphids Stegophylla brevirostris Quednau and Diphyllaphis microtrema Quednau (Insecta: Hemiptera: Aphididae) - Susan E. Halbert (EDIS)
Woolly oak aphids are conspicuous pests on oak, because they are covered with large amounts of flocculent wax. Two genera of woolly oak aphids occur in Florida, each including one known native Florida species. One species, Stegophylla brevirostris Quednau, is common, and the other, Diphyllaphis microtrema Quednau, is rare. This 3-page fact sheet was written by Susan E. Halbert, and published by the UF Department of Entomology and Nematology, October 2013. http://edis.ifas.ufl.edu/in1011